In-Vitro Anthelmintic Activity Of Leaves Of Solanam Pubescens And Gymnosporia Emerginata - UMA VASIREDDY; HEMAMALINI. K; VAMSHI. G; HARINATH. K; VISHNU VARDHAN. E; NAGARJUN GOUD. A; RAGHU. H; SHARATH GOUD. T. (International Journal of Pharma and Bio Sciences, 2011)
Southern Eastern ghats in hill region of Tirupathi is inhabited by several tribes and they are using several plants or plant based preparations for the treatment of various ailments in their traditional system of medicine. During our course of studies on ethnomedicine of this region, the plant being used as anthelmintic is solanam pubescens and gymnosporia emerginata. These plants has a wide reputation among natives of being curative for intestinal –worm infections in the form of aqueous extract. Based on this, an attempt has been made to evaluate the anthelmintic potential of this plant. The methanolic extract of solanam pubescens and gymnosporia emerginata leaves was investigated for anthelmintic activity using earthworms phertima posthuma. Various concentrations (10 – 35 mg /ml) of plant extract were tested in bioassay. Piperazine citrate (10mg/ml) was used as reference standard drug whereas distilled water as control. Determination of paralysis time and death time of the worms were recorded. Extract exhibited significant anthelmintic activity at highest concentration of 50 mg/ml. the result shows that methanolic extract possess vermicidal activity and found to be effective as an anthelmintic.